2022
DOI: 10.1136/bmjopen-2022-065296
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of self-perceived risk of falls among hospitalised adults in China: an observational study

Abstract: ObjectiveTo evaluate the accuracy of self-perceived risk of falls in hospitalised adults and explore factors associated with the differences.DesignCross-sectional study.SettingWe conducted the study in two tertiary general hospitals located in Zhejiang province and Shandong province in China.Participants339 patients were recruited using convenient sampling. The majority of them were men (54%), aged 61–70 (40.1%) and had received secondary school education or lower (82%).Outcome measuresThe Fall Risk Perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…In this study, there was no relationship between age and underestimation of fall risk, and there was a lower rate of overestimation of fall risk in the group aged 71 years or older. However, there were differences between the departments of the patients included in previous studies (Bao et al, 2022;Sakurai et al, 2013) and in this study. Therefore, future research is required to determine the relationship between age and fall risk perception among patients with various diseases.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In this study, there was no relationship between age and underestimation of fall risk, and there was a lower rate of overestimation of fall risk in the group aged 71 years or older. However, there were differences between the departments of the patients included in previous studies (Bao et al, 2022;Sakurai et al, 2013) and in this study. Therefore, future research is required to determine the relationship between age and fall risk perception among patients with various diseases.…”
Section: Discussionmentioning
confidence: 62%
“…A scoping review reported a disparity between patients' perceived fall risk and the actual risk of falling; approximately one‐third of the participants accurately identified their fall risk (Dabkowski et al., 2022). A recent study showed that approximately 62% of patients' fall assessments were consistent with the nurses' fall risk assessment regarding their fall risk, 27.5% of patients' fall assessments underestimated their fall risk, and 10.6% of patients' fall assessments overestimated their fall risk (Bao et al., 2022). Therefore, it is necessary to identify factors associated with the congruency between a patient's perception of fall risk and the fall risk assessed by healthcare professionals to ensure that patients have an accurate perception of fall risk.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Lim et al (2018) revealed that among hospitalized patients aged 65 and above in Singapore, only 31.3% accurately perceived their fall risk, while 50.7% overperceived and 18% underperceived it. In a similar vein, research by Bao et al (2022) on Chinese hospitalized patients aged over 18 found that 27.5% underperceived and 10.6% overperceived their fall risk. It has been established that individuals with perception biases are at a heightened risk of recurrent falls ( Gálvez-Barrón et al, 2013 ), while accurate perception has been shown to reduce the incidence of falls by up to 50% ( Christiansen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 81%
“…From the perspective of Proactive Health theory, patients can recognize the risk of falls and proactively develop an awareness of prevention, then such proactive behavior serves as an intrinsic motivator for effective fall management and care. However, various factors including education level, age and medication use ( Souza et al, 2022 ) can influence the consistency between perceived and objective fall risk, which is called “perceived bias” ( Bao et al, 2022 ). Perception bias has been noted that both underperceived and overperceived the risk of falls can be detrimental ( Aycock et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The total score ranges between 0 and 125, with a cut-off score of ≥ 45. In this study, we defined ≥ 45 as indicative of a high fall risk, 25—45 as indicative of a moderate fall risk, and < 25 as indicative of a low fall risk [ 22 ].…”
Section: Methodsmentioning
confidence: 99%